BIG DATA CYBER-SECURITY BASED ON A BI-OBJECTIVE HYPER-HEURISTIC SUPPORT VECTOR MACHINES - REDDY, PRANAV; Hameed,C, Shahul (International Journal of Psychosocial Rehabilitation, 2020)
This paper portrays a fundamental, capable computation to discover all occasions of any of a predetermined number of watchwords in a string of text. The count involves con-structing a constrained state configuration planning machine from the catchphrases and a short time later using the model organizing machine to process the substance string in a lone pass. Improvement of the model organizing machine requires some speculation relating to the total length of the catchphrases. The amount of state changes made by the model organizing machine in setting up the substance string is self-governing of the amount of catchphrases. The estimation has been used to improve the speed of a library bibliographic chase program by a factor of 5 to 10.